Financial Technologies: Digital Payment Systems and Digital Banking - Today's Dynamics - Sandeep Katuri, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the rapid advancement of financial technologies (FinTech), highlighting their transformative role in enhancing transaction efficiency and security across global financial markets. The integration of artificial intelligence and machine learning in financial services has revolutionized fraud detection, credit assessment, and customer service delivery while presenting new implementation challenges. As digital payment systems and banking platforms continue to evolve from early electronic transfers to sophisticated mobile applications and neobanks, they reshape traditional financial models and expand access to previously underserved populations. The interplay between emerging technologies like distributed ledger systems, cloud computing, and biometric authentication creates a dynamic ecosystem where established institutions and innovative startups both compete and collaborate. Regulatory frameworks worldwide adapt to balance innovation facilitation against consumer protection, while specialized compliance technologies address increasingly complex requirements. Despite cybersecurity threats including data breaches and ransomware attacks, advanced security measures provide essential protection for the digital financial landscape.
Keywords: Artificial Intelligence; Blockchain; Cybersecurity; Financial Inclusion; Regulatory Compliance